Indonesian Students Adaptation to Culture Shock: A Case Study of Erasmus Mundus Joint Master's Degree Students - European Union - Anom, Erman; Mayagita, Avradya (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Currently, the number of Indonesian students who receive scholarships to continue their studies in Europe is increasing day by day. They managed to get scholarships not only from the Indonesian government but also from the governments of European countries that are members of the European Union. One of the scholarship programs that are in great demand by Indonesian students is the Erasmus Mundus Program with its uniqueness, namely that each student must attend education in 3 countries in Europe. This study aims to answer questions about why culture shock is experienced by Indonesian students who are recipients of the Erasmus Mundus scholarship and how Indonesian students who receive the Erasmus Mundus scholarship overcome culture shock in order to be able to adapt to a new environment. This research is a qualitative research with a case study approach. Data was collected through semi-structured interviews and in a fluid atmosphere. In this study, as many as 5 Indonesian students received the European Union Erasmus Mundus scholarship to take a Postgraduate program in Europe. The results of this study prove that adaptation can be done through 5 factors, namely personal communication, host social communication, ethnic social communication, environment, and predisposition.